Appropriate management of cervical lymph nodes in patients with papillary thyroid cancer - Ahmad Mahmoud Abdelghany Bahr; Abdelghany Mohamed Abdelghany; Gamal Amira Mohamed; Hatem Ahmed Aboulkassem (Cairo : Ahmad Mahmoud Abdelghany Bahr, 2009)
The aim of this work is to give a high lights on appropriate management of cervical lymph nodes in patients with papillary thyroid cancer ( PTC ) it is found that gross nodal disease occurs in 20 - 30% of adult cases of PTC and is certainly justification for lymph node dissection
Thesis (M.Sc.) - Cairo University - National Cancer Institute - Department of Oncology - Surgical
Issued also as CD
Keywords: Anatomy; Introduction; Pathology